IMPLEMENTASI MANAJEMEN PENGOLAHAN LIMBAH KONSTRUKSI DALAM MEWUJUDKAN GREEN CONSTRUCTION (Studi Kasus : Pembangunan Transmart Carrefour Padang) - Mei Brilian Harefa (Universitas Quality, 2020)
Nowadays, the development of construction continues to increase every year so as to give impact there is environment. Construction projects in major cities that continue to evolve require an effort in the form of green construction implementation. The reason for the implementation of green construction is to be able to realize the development of environmentally friendly environment. Also, in a development project will produce considerable waste that will have an impact on the environment. It needs to be an effort in the form of management of waste construction so that it can realize green construction. This research aims to know the project development of Transmart Carrefour Padang already implementing Green Construction, analyzing the process of waste management construction of the development of Transmart Carrefour Padang to realize the Green construction and type of construction waste generated on the construction of Transmart Carrefour Padang. The method used to obtain research data is the observation, documentation, interviews to speakers or informants on the management of construction waste processing conducted by Transmart Carrefour Padang. The results of the research gained that in general, the project executing contractor for Transmart Carrefure Padang has been implementing green construction. So it was concluded that the implementation of construction waste management implementation to realize green construction has been good or according to standards. Waste management process using reuse, reduce, recycle and landfill. That is quite effective in reducing the onset of construction waste. The kind of construction waste produced in the construction of Transmart Carrefour Padang is solid waste of 50%, liquid waste by 30% and gas waste by 20%.